PACE-Learning uses Local Culture-Based Learning Videos for KMBKS Association Youth: PACE-Learning menggunakan Video Pembelajaran berbasis Budaya Lokal bagi Pemuda Ikatan KMBKS - Lulu Jola Uktolseja; Melda Agnes Manuhutu; Ratna Rosmauli Pakpahan (Universitas Lancang Kuning, 2023)
The unification of education and social affairs is an integration and efficiency technique so that the object, namely KMBKS youth, can learn English with fun while studying Papuan culture. Community Service Method for Learning English through the implementation of Productive, Active, Creative English (PACE) Learning using animated English learning videos which can also be studied through the English Online Study Room, Papuan Socio-Cultural based for English language training and awareness: cultural introduction Papua. At the end of this activity, the result was that there was an increase in English language skills as measured by the Pre-Test and Post-Test. Based on the Kahoot results, participants were very enthusiastic and enthusiastic about carrying out PACE activities during the specified time. This community service activity is a real effort to increase the harmony of life between ethnic groups living in Sorong City and also improve the English language skills of the youth of the KMBKS tribe. This activity also trains participants to learn independently, improve social relationships and motivate one's life goals.